2013
DOI: 10.1016/j.str.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Atomic Force Microscopic Observation of ATP-Dependent Rotation of the AAA+ Chaperone p97

Abstract: p97 (also called VCP and CDC-48) is an AAA+ chaperone, which consists of a substrate/cofactor-binding N domain and two ATPase domains (D1 and D2), and forms a homo-hexameric ring. p97 plays crucial roles in a variety of cellular processes such as the ubiquitin-proteasome pathway, the endoplasmic reticulum-associated protein degradation, autophagy, and modulation of protein aggregates. Mutations in human p97 homolog VCP are linked to neurodegenerative diseases. The key mechanism of p97 in these various function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
(50 reference statements)
4
36
0
Order By: Relevance
“…Extensive classification revealed that it is structurally homogeneous in the presence of ADP and its six-fold symmetrical, compact structure is essentially identical to that of full-length p97 determined by X-ray crystallography [7] and SAXS [12]. A relative rotation of the D1 and D2 domains, as described in AFM experiments in the presence of ATP or ADP [13], were not seen in any of the cryo-EM maps determined here.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Extensive classification revealed that it is structurally homogeneous in the presence of ADP and its six-fold symmetrical, compact structure is essentially identical to that of full-length p97 determined by X-ray crystallography [7] and SAXS [12]. A relative rotation of the D1 and D2 domains, as described in AFM experiments in the presence of ATP or ADP [13], were not seen in any of the cryo-EM maps determined here.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, the AMP-PNP density shows a well-defined density segment (Fig. 3B), for which the fitted atomic model suggests that it corresponds to the very N-terminal residues (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These N-terminal 20 residues are absent from all p97 crystal structures but one protomer of the ATPcS-bound IBMPFD mutant A232E, which includes residues 12-20 [10].…”
Section: Conformational Changes Of the N-d1 Segmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the 2D crystal surface has been used for HS-AFM imaging of actin polymerization processes at the plus and minus ends of an actin filament, 37 dynamic association and dissociation between GroEL and GroES, 37 Ca 2+ -induced conformational changes of calmodulin, 37 and ATP-invoked structural changes of an AAA ATPase, p97. 102 For monomeric proteins, the tethering to the surface through a single biotin binding site is locally fixed but can result in a rotational motion around the link. This mobility can however be reduced using reactive dibiotin compounds.…”
Section: Substrate Surfacesmentioning
confidence: 99%
“…For example, the radii of gyration of the nucleotide-free, AMP-PNP, ADP-AlF x and ADP states determined by SAXS are 61, 57, 55 and 58 Å, respectively. Furthermore, high speed atomic force microscopy revealed that ATP binding to the D2 domain induces forward clockwise and backward counterclockwise rotational movements (23 ± 8°) between the N-D1 and D2 hexameric rings [31]. The repeated back and forward rotational movements of p97 suggest a possible way of converting the chemical energy stored in ATP into mechanical energy required for the remodeling of substrates (see below).…”
Section: P97 Structure and Atpase Activitymentioning
confidence: 99%